Intensity‐modulated radiotherapy (IMRT) in pediatric low‐grade glioma. Issue 14 (30th April 2013) - Paulino, Arnold C.; Mazloom, Ali; Terashima, Keita; Su, Jack; Adesina, Adekunle M.; Okcu, M. Faith; Teh, Bin S.; Chintagumpala, Murali
<x xml:space="preserve">Abstract</x> BACKGROUND The objective of this study was to evaluate local control and patterns of failure in pediatric patients with low‐grade glioma (LGG) who received treatment with intensity‐modulated radiation therapy (IMRT). METHODS In total, 39 children received IMRT after incomplete resection or disease progression. Three methods of target delineation were used. The first was to delineate the gross tumor volume (GTV) and add a 1‐cm margin to create the clinical target volume (CTV) (Method 1; n = 19). The second was to add a 0.5‐cm margin around the GTV to create the CTV (Method 2; n = 6). The prescribed dose to the GTV was the same as dose to the CTV for both Methods 1 and 2 (median, 50.4 grays [Gy]). The final method was dose painting, in which a GTV was delineated with a second target volume (2TV) created by adding 1 cm to the GTV (Method 3; n = 14). Different doses were prescribed to the GTV (median, 50.4 Gy) and the 2TV (median, 41.4 Gy). RESULTS The 8‐year progression‐free and overall survival rates were 78.2% and 93.7%, respectively. Seven failures occurred, all of which were local in the high‐dose (≥95%) region of the IMRT field. On multivariate analysis, age ≤5 years at time of IMRT had a detrimental impact on progression‐free survival. CONCLUSIONS IMRT provided local control rates comparable to those provided by 2‐dimensional and 3‐dimensional radiotherapy. Margins ≥1 cm added to the GTV may not be necessary, because excellent local control was achieved by adding a 0.5‐cm margin (Method 2) and by dose painting (Method 3). Cancer 2013;119:2654–2659. © 2013 American Cancer Society.